Fault detection filtering for nonlinear switched systems via event-triggered communication approach. (March 2019) - Liu, Xinxin; Su, Xiaojie; Shi, Peng; Nguang, Sing Kiong; Shen, Chao
Abstract: This paper considers the fault detection problem for networked switched control systems subject to repeated scalar nonlinearities and stochastic disturbance under an event-triggered scheme. A nonlinear fault detection filter is proposed to generate the residual signal and detect system faults, and an event-triggered strategy is applied to limit signal transmission. Sufficient conditions to guarantee an event-based residual system is mean-square exponentially stable with the desired performance are obtained using average dwell time stability theory and a positive diagonally dominant Lyapunov functional approach. The corresponding fault detection mechanism parameters are calculated using the linearization technique. The event-triggered fault-detection filter and controller coordinated design are extended and then applied to cognitive radio networks. Two examples are provided to verify the proposed new design method.